Geologic map of Seward Peninsula, Alaska / U.S. Geological Survey, compiled and arranged by Philip s. Smith - Smith, Philip S. (Philip Sidney), 1877-1949 (Washington, D.C. : Geological Survey (U.S.), 1913)
"Water-supply paper 314, plate iv." Color 1:1:500,000